MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP HASIL BELAJAR IPA TEMA PERKEMBANGBIAKAN HEWAN PADA ANAK TUNARUNGU KELAS V - FIRDAUSI, ALFIANA; PURBANINGRUM, ENDANG (Jurnal Pendidikan Khusus, 2018)
The hearing impairment not only caused the lack of speaking ability development but also influenced toward the speech ability. Because of little information accepted by the children it had impact to the learning result. It was required learning which was suitable with the children?s characteristics. The model of quantum learning utilized more the visual sense in the learning. This research had purpose to analyze the influence of quantum learning model toward learning science result, especially in animal proliferation theme. This research applied quantitative approach with pre experiment kind and the arrangement of one group pre test ? post test design. The subject of this research was hearing impairment children class V numbering 8 people. The research location was in SDLB-B Karya Mulia I Surabaya. The technique of data collection was test with the analysis technique of statistic non parametric data used the formula of wilcoxon match pairs test. The result of data research indicated that the usage of quantum learning model significantly influenced toward learning science result of animal proliferation theme to hearing impairment children class V in SDLB-B Karya Mulia I Surabaya. Keywords: quantum learning method, learning result, science, hearing impairment children